CHARACTERIZATION OF PHYSICOCHEMICAL PROPERTIES OF SOLID LAUNDRY SOAP BASED ON LERAK (Sapindus rarak DC.) - La Choviya Hawa; Aini Nurrachmani Bahari; Anang Lastriyanto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Lerak (Sapindus rarak DC.) is one of the fruits with a main active compound called saponin. Saponins function as natural surfactants with foaming and emulsifying properties. Lerak in Indonesia is widely used as a traditional detergent. Using lerak essence as a detergent, batik washing can be done well without fading colors and is more environmentally friendly. Lerak essence can be applied as an additional component in preparing solid laundry soap. Adding lerak essence is to replace the anionic surfactant Sodium Lauryl Sulfate (SLS). Therefore, the risk of pollution can be lowered, as well as keep batik cloth from easily fading out. This study was conducted using Randomized Block Design (RBD) with two factors, including the concentration of lerak essence (10%, 7.5%, and 5%) and NaOH molecules (0.5 mol and 0.375 mol). This study aimed to analyze the effect of variation in lerak essence concentration and NaOH molecular on the physicochemical properties of solid laundry soap. The results showed that the higher the concentration of lerak essence and NaOH molecules, the more it reduces the water content in solid laundry soap. Concentrations of 10% lerak essence and 0.5 mol NaOH molecules have the highest value for foam stability and the lowest value for moisture content. Among the tensile strength, pH, brightness level and yellowness level, the highest value was in the concentration of 7.5% lerak essence and 0.5 mol NaOH molecules. Treatments of the variation of lerak essence concentrations significantly affect pH, while the treatment of NaOH molecular variation significantly affects pH, tensile strength, foam stability, brightness level (L*) and yellowness level (b*)